Keeping Your Distance - Glen Gatin (Grounded Theory Review: An International Journal)
This analysis began with inquiries into the substantive area of distance education using the classic grounded theory method. Analysis revealed a pattern of problem-solving behavior, from which the theory Keeping Your Distance emerged. The theory is an integrated set of concepts referring to the conscious and unconscious strategies that people use to regulate distance, physical and representative, in their everyday lives. Strategies are used to control physical, emotional, and psychological realities and to conserve personal energy in interactions with individuals and/or institutions. For all social interactions, people use a personalized algorithm of engagement that mitigates conditions and consequences and preserves optimal distance. Keeping Your Distance provides a theoretical starting point for considerations of the changing notions of distance. In part, these changes have been brought about by developments in the fields of Information and Communication Technology (ICT) and online social networking.